Yours from the tower - Nicholls, Sally, 1983- (2024)
"In 1896, three best friends--Tirzah, Sophia and Polly--who are leading very different lives after boarding school share their dreams, hopes, frustrations and romances through a series of letters as they search for happiness and love near the dawn of the Edwardian era"--
Keywords: Young women -- Juvenile fiction; Female friendship -- Juvenile fiction; Letters -- Juvenile fiction; Young women -- Fiction; Female friendship -- Fiction; Letters -- Fiction; Great Britain -- History -- Edward VII, 1901-1910 -- Juvenile fiction; Great Britain -- History -- Edward VII, 1901-1910 -- Fiction; Historical fiction; Epistolary fiction; Novels